Thermo-mechano-chemical modeling and computation of thermosetting polymers used in post-installed fastening systems in concrete structures - Abali, Bilen Emek; Vorel, Jan; Wan-Wendner, Roman (Continuum mechanics and thermodynamics, 2023)
As thermoset polymers find frequent implementation in engineering design, their application in structural engineering is rather limited. One key reason relies on the ongoing curing process in typical applications such as post-installed adhesive anchors, joints by structural elements or surface-mounted laminates glued by adhesive polymers. Mechanochemistry including curing and aging under thermal as well as mechanical loading causes a multiphysics problem to be discussed. For restricting the variety of material models based on empirical observations, we aim at a thermodynamically sound strategy for modeling thermosets. By providing a careful analysis and clearly identifying the assumptions and simplifications, we present the general framework for modeling and computational implementation of thermo-mechano-chemical processes by using open-source codes.
Keywords: Curing; Finite element method (FEM); Thermosetting polymers; Thermomechanics; Continuum mechanics